2008
DOI: 10.1007/s00259-008-0979-7
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine transporter availability in Parkinson’s disease patients with or without depression

Abstract: Our data indicate that depression in PD is associated with a more pronounced loss of striatal dopamine transporter availability that is most likely secondary to increased dopaminergic degeneration. In addition, depressed PD patients have a lower availability of midbrain/brainstem monoamine transporters than nondepressed PD patients. These findings provide in vivo evidence in support of the known post-mortem data demonstrating more extensive nerve cell loss in PD with depression and indicate that SPECT imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 40 publications
5
45
0
1
Order By: Relevance
“…Consistent with this hypothesis, depression in PD was associated with a more pronounced loss of dopamine transporter availability in the striatum in PD (Hesse et al, 2009) and in the right nucleus caudatus in DLB (Roselli et al, 2009), most likely secondary to dopaminergic degeneration. However, the lack of association with parkinsonism in our study argues against an association between depression and striatal dopaminergic deficits, although an association with pre-frontal dopaminergic deficit is possible.…”
Section: Discussionmentioning
confidence: 51%
“…Consistent with this hypothesis, depression in PD was associated with a more pronounced loss of dopamine transporter availability in the striatum in PD (Hesse et al, 2009) and in the right nucleus caudatus in DLB (Roselli et al, 2009), most likely secondary to dopaminergic degeneration. However, the lack of association with parkinsonism in our study argues against an association between depression and striatal dopaminergic deficits, although an association with pre-frontal dopaminergic deficit is possible.…”
Section: Discussionmentioning
confidence: 51%
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The relative anatomic segregation between striatal DAT and extrastriatal SERT binding sets the condition for 123 I-FP-CIT SPECT studies to examine also SERT in vivo. Interestingly, recent clinical FP-CIT SPECT studies showed not only loss of striatal DAT but also loss of midbrain SERT binding in dementia with Lewy bodies and in Parkinson patients with depression (6,7). In these 2 studies, 123 I-FP-CIT binding in SERT-rich areas was measured 3 h after injection, but it is not known whether this time point is optimal for assessing FP-CIT binding to SERT.…”
mentioning
confidence: 99%